2019
DOI: 10.3390/polym11020233
|View full text |Cite
|
Sign up to set email alerts
|

Development of Flame-Retarded Nanocomposites from Recycled PET Bottles for the Electronics Industry

Abstract: Recycled polyethylene-terephthalate (rPET) nanocomposites of reduced flammability were prepared by combining aluminum-alkylphosphinate (AlPi) flame retardant (FR) and natural montmorillonite (MMT), in order to demonstrate that durable, technical products can be produced from recycled materials. During the development of the material, by varying the FR content, the ratio and the type of MMTs, rheological, morphological, mechanical and flammability properties of the nanocomposites were comprehensively investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Currently, halogen‐free flame‐retarded PET systems arouse more and more attention in flame‐retardant area. Flame retardants containing P, N, B, and Si elements are reported more environmental‐friendly and effective for PET material …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, halogen‐free flame‐retarded PET systems arouse more and more attention in flame‐retardant area. Flame retardants containing P, N, B, and Si elements are reported more environmental‐friendly and effective for PET material …”
Section: Introductionmentioning
confidence: 99%
“…B, and Si elements are reported more environmental-friendly and effective for PET material. [8][9][10][11] Melamine polyphosphate (MPP), an efficacious P-N flame retardant, is broadly applied in improving the flame retardance of poly (vinyl alcohol), polyamide 6,6, and epoxy resin because of its excellent thermal stability, low cost, and low smoke and toxicity. [12][13][14] Previously reported studies have demonstrated that MPP can act both in gaseous and condensed phases.…”
mentioning
confidence: 99%
“…With addition of 4% mass Co-OMt, 4% mass Co-OMt/IFR/PP nanocomposites have surpassed a UL-94 V-0 rating, with an LOI value as high as 32.1%. e use of MMT as a synergic additive to flame retardants for designing polymers with better flame-retardant properties has already been extensively studied [45,[153][154][155][156][157][158][159][160][161][162][163][164][165][166]. e effect of APP/zinc borate (ZB) for making highly efficient flame retardants and ceramics of ethylene-vinyl acetate/mica powder/organic modified montmorillonite (EVA/MP/OMMT) composites has been shown [166].…”
Section: Black Phosphorus and Dehydrated Vanadylmentioning
confidence: 99%
“…The usage of poly(ethylene terephthalate) (PET) still increases nowadays; in original form and as secondary raw material alike [1,2]. Besides the packaging industry, PET is increasingly used as a technical material thanks to the achievements of the material developments (Solid State Polycondensation reaction (SSP) or chain extender additives) and the advancements in the processing technologies (foam forming, 3D printing) [3][4][5][6][7]. Regarding applicability of the final products the mechanical properties are crucial, which are greatly affected by the morphology and crystalline structure formed during processing [8,9].…”
Section: Introductionmentioning
confidence: 99%